Spatial migration of human reward processing with functional development: Evidence from quantitative meta‐analyses - Yaple, Zachary A (Hum Brain Mapp, 2020)
Functional magnetic resonance imaging (fMRI) studies have shown notable age‐dependent differences in reward processing. We analyzed data from a total of 554 children, 1,059 adolescents, and 1,831 adults from 70 articles. Quantitative meta‐analyses results show that adults engage an extended set of regions that include anterior and posterior cingulate gyri, insula, basal ganglia, and thalamus. Adolescents engage the posterior cingulate and middle frontal gyri as well as the insula and amygdala, whereas children show concordance in right insula and striatal regions almost exclusively. Our data support the notion of reorganization of function over childhood and adolescence and may inform current hypotheses relating to decision‐making across age.